PERLINDUNGAN HUKUM TERTANGGUNG PASCA PUTUSAN MAHKAMAH KONSTITUSI PERUBAHAN PASAL PEMBATALAN SEPIHAK - Tjwan, Go Chin; Ang, Ferdian Handoyo; Lianto, Anthony (Faculty of Law, Universitas Tanjungpura, 2026)
Abstract Constitutional Court Decision Number 83/PUU-XXII/2024 has strengthened the principle of protection for insured parties in health insurance contracts, but at the same time it also creates legal uncertainty regarding the legitimacy of the cancellation or non-renewal of the policy carried out unilaterally by the insurer in the event of concealment of the circumstances. This article analyzes how the validity of these actions after the Constitutional Court's decision is based on contract law, insurance law, and consumer protection law, which previously in Article 251 of the Commercial Code, concealment of circumstances resulted in the cancellation of insurance. Using a normative legal method through analysis of legislation, court decisions, and legal doctrine, this study emphasizes the role of the principle of good faith and the protective function of insurance contracts. The results of the study show that after Constitutional Court Decision Number 83/PUU-XXII/2024, Cancellation or rejection of a health insurance policy extension must be made based on an agreement between the parties or based on a court decision, and termination or rejection of a policy extension carried out unilaterally is invalid. Abstrak Putusan Mahkamah Konstitusi Nomor 83/PUU-XXII/2024 telah memperkuat prinsip perlindungan tertanggung dalam kontrak asuransi kesehatan, namun di saat bersamaan juga menimbulkan adanya ketidakpastian hukum mengenai legitimasi pembatalan atau tidak diperpanjangnya polis yang dilakukan secara sepihak oleh penanggung dalam hal terjadi penyembunyian keadaan. Artikel ini menganalisis bagaimana keabsahan tindakan tersebut pasca putusan MK berdasarkan hukum kontrak, hukum perasuransian, dan hukum perlindungan konsumen, yang sebelumnya dalam Pasal 251 Kitab Undang-Undang Hukum Dagang, penyembunyian keadaan mengakibatkan pembatalan pertanggungan. Dengan menggunakan metode yuridis normatif melalui analisis peraturan perundang-undangan, putusan pengadilan, dan doktrin hukum, penelitian ini menekankan peran asas itikad baik dan fungsi protektif kontrak asuransi. Hasil penelitian menunjukkan bahwa setelah Putusan MK Nomor 83/PUU-XXII/2024, pembatalan atau penolakan perpanjangan polis asuransi kesehatan harus dilakukan berdasarkan kesepakatan para pihak atau berdasarkan Putusan Pengadilan, dan pengakhiran atau penolakan perpanjangan polis yang dilakukan secara sepihak adalah tidak sah.